Perceptions of slow codes by nurses working on internal medicine wards. (September 2019) - Ganz, Freda DeKeyser; Sharfi, Rotem; Kaufman, Nehama; Einav, Sharon
Background: Cardio-pulmonary resuscitation is the default procedure during cardio-pulmonary arrest. If a patient does not want cardio-pulmonary resuscitation, then a do not attempt resuscitation order must be documented. Often, this order is not given; even if thought to be appropriate. This situation can lead to a slow code, defined as an ineffective resuscitation, where all resuscitation procedures are not performed or done slowly. Research objectives: To describe the perceptions of nurses working on internal medicine wards of slow codes, including the factors associated with its implementation. Research design: This was a cross-sectional, descriptive study. Participants completed a personal characteristics questionnaire and the Perceptions and Factors of Slow Codes questionnaire designed for this study. Participants and research context: The sample was a convenience sample of nurses working on internal medicine wards in two Israeli hospitals. Ethical considerations: The study received ethical approval from both institutions, where data were collected and stored according to institutional policy. Findings: Most reported that resuscitations were conducted according to protocol (n = 90, 76.2%). Some took their time calling the code (n = 22, 18.3%), or waited by the bedside and did not perform cardio-pulmonary resuscitation (n = 45, 37.5%). Factors most associated with slow codes were poor patient prognosis (mean = 3.52/5, standard deviation = 1.27) and a low chance of patient survival (mean = 3.37/5, standard deviation = 1.21). Two-thirds (n = 76, 66.8%) reported that slow codes were done on their unit and the majority (n = 80, 69%) perceived slow codes as ethical. Discussion: This study confirms that slow codes are part of medical care on internal medicine wards, where most nurses perceive them as an ethical alternative. These perceptions are in contrast to most legal and ethical opinions expressed in the literature. Conclusion: Nurses should be educated about the legal and ethical implications of slow codes, and qualitative and quantitative studies should be conducted that further investigate its implementation.